Can Cerebral Regional Oxygen Saturation (rSO2) Be Used as an Indicator of the Quality of Chest Compressions in Patients With Cardiopulmonary Arrest? A Study Evaluating the Association Between rSO2 and Mean Arterial Pressure: The PRESS Study - Kishihara, Yuki; Yasuda, Hideto; Kashiura, Masahiro; Harada, Naoshige; Moriya, Takashi (Frontiers in Medicine, 2022)
Introduction Sudden cardiac arrest causes numerous deaths worldwide. High-quality chest compressions are important for good neurological recovery. Arterial pressure is considered useful to monitor the quality of chest compressions by the American Heart Association. However, arterial pressure catheter might be inconvenient during resuscitation. Conversely, cerebral regional oxygen saturation (rSO2) during resuscitation may be associated with a good neurological prognosis. Therefore, we aimed to evaluate the correlation between mean arterial pressure and rSO2 during resuscitation to evaluate rSO2 as an indicator of the quality of chest compressions. Materials and Methods This study was a single-center, prospective, observational study. Patients with out-of-hospital cardiac arrest who were transported to a tertiary care emergency center in Japan between October 2014 and March 2015 were included. The primary outcome was the regression coefficient between mean arterial pressure (MAP) and rSO2. MAP and rSO2 were measured during resuscitation (at hospital arrival [0 min], 3, 6, 9, 12, and 15 min), and MAP was measured by using an arterial catheter inserted into the femoral artery. For analysis, we used the higher value of rSO2 obtained from the left and right forehead of the patient measured using a near-infrared spectrometer. Regression coefficients were calculated using the generalized estimating equation with MAP and systolic arterial pressure as response variables and rSO2 as an explanatory variable since MAP and rSO2 were repeatedly measured in the same patient. Since the confounding factors between MAP or systolic arterial pressure and rSO2 were not clear clinically or from previous studies, the generalized estimating equation was analyzed using a univariate analysis. Results In this study, 37 patients were analyzed. The rSO2 and MAP during resuscitation from hospital arrival to 15 min later were expressed as follows: (median [interquartile range, IQR]): rSO2, 29.5 (24.3–38.8)%, and MAP, 36.5 (26–46) mmHg. The regression coefficient (95% CI) of log-rSO2 and log-MAP was 0.42 (0.03–0.81) (p = 0.035). Conclusion The values of rSO2 and MAP showed a mild but statistically significant association. rSO2 could be used to assess the quality of chest compressions during resuscitation as a non-invasive and simple method.